2022
DOI: 10.31234/osf.io/p748g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Regulatory Strategy Use, Efficacy, and Strategy-Situation-Fit in Self-Control Conflicts of Initiation, Persistence, and Inhibition

Abstract: Self-control is the ability to (1) “override impulses to act”, (2) “make oneself initiate” and (3) “persist in boring, difficult, or disliked activity” (Carver, 2019, p. 477). We explored the self-regulatory strategies that people use for these three types of self-control conflicts and their subjective efficacy as a function of conflict type. In addition, we hypothesized that people who more frequently create strategy-situation fit by tying strategies to the conflict types they are effective for, are more succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Specifically, the subscale of hedonic success should be related to the preference for aesthetic hedonic dishes, as it captures ability to relax and go astray from focal goal pursuit. Based on recent findings (Wenzel et al, 2022), self-regulatory strategies and orientations contingent with the different types of self-control conflicts are more effective for goal conflict resolution. Self-regulatory success is a function of individual differences and the situations at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the subscale of hedonic success should be related to the preference for aesthetic hedonic dishes, as it captures ability to relax and go astray from focal goal pursuit. Based on recent findings (Wenzel et al, 2022), self-regulatory strategies and orientations contingent with the different types of self-control conflicts are more effective for goal conflict resolution. Self-regulatory success is a function of individual differences and the situations at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that people do indeed spontaneously use a variety of different strategies in their everyday lives and that many strategies can be effective (Bürgler et al, 2021;Hennecke & Bürgler, 2020;Hennecke et al, 2019;Lopez et al, 2021;Milyavskaya et al, 2020;Wenzel et al, 2022). People also frequently use multiple strategies within a single self-control conflict.…”
Section: Metacognitive Processes During a Self-control Conflict: Regu...mentioning
confidence: 99%